Calibration of the science process skills among Malaysian elementary students: A Rasch model analysis - Nazahiyah Mustafa; Ahmad Zamri Khairani; Nor Asniza Ishak (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study aimed to calibrate the test items of science process skills used as a test at primary school students to provide information on the difficulty of each item. Data were collected from 128 standard five students in a primary school in Penang. The test was given in multiple-choice as many as 40 items consisting of 33 items partial credit test was developed to gather information from the students. The analysis included an assessment of the model’s assumptions and calibrations according to the individual items. Information on the Rasch calibration according to the topic were provided. Results revealed that the measurement made fulfilled both model-data fit and unidimensionality assumptions. Further analysis showed that observing and communicating were endorsed as the easiest to master while inferring and classifying were the most challenging. The study discussed the implication, particularly towards the teaching and learning of science process skills in the classroom. Teachers should seriously consider the science process skills when designing their teaching and learning strategies in the classroom.